The Association of Gender with the Patterns of Impactions and Associated Radiolucency’s in Mandible and Maxilla - Butt, Hira; Hafeez, Fatima; Tahir, Fizza; Khan, Nauman Rauf; Khawaja, Sadaf Amjad; Amjad, Aneela (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES To find the association between gender and the patterns of impactions and associated radiolucency in Mandible and Maxilla. METHODOLOGY A cross-sectional descriptive study was conducted on 385 Orthopantomograms (OPG) of patients visiting Sharif Medical and Dental College (SMDC), Services Institute of Medical Sciences (SIMS) and Institute of Dentistry, CMH, Lahore Medical College, Lahore over a period of three months from December 2020 to February 2021. The angle of the impacted third molar was classified using Winters classification. The Pell and Gregory classification was used for depth of third molar impaction and ramus relationship of mandibular third molars. Statistical analysis was done using SPSS 23 and a P value ≤ 0.05 was considered significant. RESULTS The angle of impaction and gender in impacted mandibular third molars were significantly associated with each other (p=0.011) while the depth of impaction (p=0.729), and ramus relationship(p=0.318) were not significantly associated with gender. The associa tion between gender and periapical radiolucency (p=0.605), peri coronal radiolucency (p=0.591), caries (p=0.499) and external resorption (p=0.499) were non-significant. In maxillary impacted third molars the association between gender and depth of impaction (p=0.121), angle of impaction (p=0.284), periapical radiolucency (p=0.111), peri coronal radiolucency (p=0.805) and caries (p=1.000) were non-significant. CONCLUSION In impacted mandibular third molars the periapical, peri coronal radiolucency,caries and external resorption were more in the males as compared to the females. In maxillary third molar impactions, the periapical radiolucency radiolucency was greater in males while peri coronal radiolucency was greater in females.